Requerimiento: instalación y mantenimiento de redes contra incendio para colegios distritales en la ciudad de Bogotá D.C. (2017)
This paper presents the requirements of the Colombian regulations for the installation of fire-based water-based systems in the district schools of Bogotá D.C. And is intended to investigate the approximate direct costs for 2017 of the square meter in the facility and the annual budget that would require the inspection, maintenance and testing of the fire facilities mentioned.